Field notes fall migration, 1976 - Newlon, Michael C.et al (1976)
Field notes contributed by Michael C. Newlon. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1976. Epson - sheet feed/flatbed